Grammar-Based Instruction in EFL Reading Comprehension Outcomes and Learner Perceptions - Siswoyo Siswoyo; Miftahul Janah; Dian Rakhmawati; Kania Syifa Maharani (Journal of Educational Studies, 2025)
Although grammatical competence is widely recognized as an important contributor to reading comprehension in English as a Foreign Language (EFL) context, previous studies have reported inconsistent findings regarding the effectiveness of grammar-based instruction. Moreover, limited research has simultaneously examined reading outcomes and learners’ affective responses, particularly in Indonesian higher education settings. Addressing this gap, this study investigated the impact of grammar-based instruction on EFL learners’ reading comprehension and explored their perceptions, motivation, and engagement toward this instructional approach. The novelty of this study lies in its integrated examination of cognitive and affective dimensions of grammar-based instruction within an Indonesian EFL context. A mixed-methods design was employed, combining a one-group pretest–posttest procedure with questionnaire and semi-structured interview data. The participants were 31 third-semester undergraduate students enrolled in a Reading course at the English Education Department of Universitas Muhammadiyah Pringsewu, Indonesia. Quantitative findings revealed a mean score gain of 5.16 points; however, the improvement was not statistically significant (t(30) = 2.03, p = .051). Nevertheless, a small-to-medium effect size (Cohen’s d = 0.37) indicated practical educational value. Qualitative findings generated four themes: perceived cognitive benefits of grammar-based instruction, mixed motivational and engagement responses, cognitive challenges associated with grammar processing, and learners’ preference for contextualized and multimodal grammar instruction. The findings suggest that grammar-based instruction can support EFL reading development when integrated with meaningful reading activities, differentiated according to learners’ proficiency levels, and supported through contextualized and technology-enhanced learning environments.